PHARMACOLOGICAL EVALUATION OF TRIPHALA CHURNA INSTREPTOZOTOCIN (I. C. V.) INDUCED DEMENTIA IN RATS - Deka, Purabi; Kumar, Arun (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The objective of the study was to investigate the memory improving activity of Triphala Churna hydro-methanolic fruit extract on learning and memory functions in Streptozotocin (I. C. V) induced dementia in rats by using morris water maze and elevated plus maze. Methods: A total of 42 albino wistar rats weighing 80-100 g were randomized into 7 equal groups as follows: Normal control group received normal saline (1 ml/kg p. o.) for 24 d, STZ treated group (3 mg/kg, i. c. v) were administered in two dosage regimen i.e. on first day and third day.), Standard group: Streptozotocin (3 mg/kg i. c. v)+Vitamin E (100 mg/kg/day p. o.) were administered for 21 d, Standard group: Streptozotocin (3 mg/kg i. c. v)+Rivastigmine (2 mg/kg/day p. o.) were administered for 21 d. The learning and memory-impaired rats were treated with Triphala Churna Formulation 1, Triphala Churna Formulation 2 and Triphala Churna Formulation 3 for 21 d (100 mg/kg p. o.). AchE activity, lipid peroxidation, superoxide dismutase, glutathione level of brain homogenate was estimated in Control/STZ (I. C. V)/Standard/Triphala Churna fruits extract treated rats. Results: Administration of Triphala Churna fruits extract significantly restored learning and memory impairment induced by STZ (I. C. V) in the elevated plus maze and morris water maze. Furthermore, in the TPLC F2 and TPLC F3 treated group brain AchE level was decreased (P≤0.01) as well as brain lipid peroxidation was also decreased (P≤0.001). Brain antioxidant enzymes such as glutathione level were increased (P≤0.001) in the TPLC1 and TPLC2 treated group when compared to the STZ treated group, TPLC F2 and TPLC F3 treated group showed significant (P≤0.001, P≤0.01) increase in superoxide dismutase level. Conclusion: Triphala Churna fruits extract has an improving effect on learning and memory impairment rats produced by Streptozotocin (I. C. V) and may have a useful effect in the treatment of dementia and Alzheimer's disease.